Late‐onset hypogonadism and lifestyle‐related metabolic disorders. (16th February 2020) - Braga, Patrícia C.; Pereira, Sara C.; Ribeiro, João C.; Sousa, Mário; Monteiro, Mariana P.; Oliveira, Pedro F.; Alves, Marco G.
Abstract: Background: Late‐onset hypogonadism (LOH) is a condition defined by low levels of testosterone (T), occurring in advanced age. LOH is promoted by senescence, which, in turn, has negative effects on male fertility. Interestingly, the impact of metabolic disorders on the male reproductive system has been the topic of several studies, but the association with LOH is still debatable. Objectives: Herein, we discuss the hypothesis that the prevalence of metabolic abnormalities potentiates the effects of LOH on the male reproductive system, affecting the reproductive potential of those individuals. Material and methods: We analyzed the bibliography available, until June 2019, about LOH in relation to metabolic and hormonal dysregulation, sperm quality profiles and assisted‐reproduction treatment outcomes. Results: LOH affects the hypothalamic‐pituitary testis (HPT) axis. Additionally, metabolic disorders can also induce T deficiency, which is reflected in decreased male fertility, highlighting a possible connection. Indeed, T replacement therapy (TRT) is widely used to restore T levels. Although this therapy is unable to reverse all deleterious effects promoted by LOH on male reproductive function, it can improve metabolic and reproductive health. Discussion and Conclusions: Emerging new evidence suggests that metabolic disorders may aggravate LOH effects on the fertility potential of males in reproductive age, by enhancing T deficiency. These results clearly show that metabolic disorders, such as obesity and diabetes, have a greater impact on causing hypogonadotropic hypogonadism than tissue senescence. Further, TRT and off‐label alternatives capable of restoring T levels appear as suitable to improve LOH, while also counteracting comorbidities related with metabolic diseases.